A single‐center long‐term experience with marginal donor utilization for heart transplantation. Issue 11 (18th August 2020) - Galeone, Antonella; Lebreton, Guillaume; Coutance, Guillaume; Demondion, Pierre; Schmidt, Matthieu; Amour, Julien; Varnous, Shaida; Leprince, Pascal
Abstract: Background: To evaluate the early and late outcome of heart transplantation (HT) using marginal (MDs) and optimal donors (ODs). Methods: Clinical records of recipients transplanted between July 2004 and December 2014 were retrospectively reviewed. MDs were defined as follows: age >55 years, high‐dose inotropic support, left ventricular ejection fraction <45%, left ventricular hypertrophy, donor to recipient predicted heart mass ratio <0.86, ischemic time >4 hours. Results: A total of 412 (55%) recipients received an organ from a MD; recipients who received an organ from an OD had less primary graft dysfunction (PGD) (25% vs 38%; P  < .001), less acute renal failure (23% vs 34%; P  < .001), and higher survival rates (90.2% vs 81.8% at 30 days, 79.5% vs 71.1% at 1 year, 51.8% vs 45.4% at 12 years; P  = .01) than recipients who received an organ from a MD. There was no statistically significant difference in 30‐day conditional survival between the two groups (survival rates 57.4% vs 55.5% at 12 years; P  = .43). PGD, perioperative hemodialysis, and sepsis were independent risk factors of mortality at multivariate analysis. Conclusions: Utilization of MDs for HT is associated with a higher incidence of PGD and acute renal failure, and a reduction of 30‐day survival.